The Influence of Islamic Leadership, Organizational Culture, Organizational Climate and Work Behavior on Teacher and Employee Performance - Muhammad Idris Addayan; Robi Hendra (SAINTIS Publishing, 2025)
This study aims to analyze the influence of Islamic Leadership, Organizational Culture, Organizational Climate and Work Behavior on Teacher and Employee Performance at Al-Azhar Jambi, Bungo, and Tebo. Using descriptive quantitative research methods, data were collected from 310 teachers through questionnaires distributed online. Data analysis was carried out using the Smart-PLS 4 application, which allows for effective testing of relationships between variables. Islamic leadership has a positive and significant effect on teacher and employee performance. Organizational culture has a positive and significant effect on teacher and employee performance. Islamic leadership also has a significant positive effect on work behavior, with the Organizational Climate coefficient having a significant effect on work behavior. Work behavior shows a very strong and significant effect on teacher and employee performance.